EFFECT OF INCREASING FOOD COMMODITY PRICES AGAINST INFLATION IN MEDAN CITY - Dini Khairina Pasaribu; Iskandarini; Rahmanta (CV. Radja Publika, 2024)
Inflation is a situation where the prices of goods and services generally increase over a certain period of time. High and unstable inflation is a reflection of economic instability which results in a general and continuous increase in the price level of goods and services, and results in increasing levels of goods and services. Inflation in food can be caused by various factors, including fluctuations in the price of agricultural raw materials such as grain prices, adverse weather conditions such as drought or floods that affect agricultural production, increases in production costs such as energy and fertilizer costs, changes in global or local demand, trade policies, market speculation, and other factors. The aim of this research is to identify the influence of corn prices, soybean prices, chicken prices, garlic prices on inflation in Medan City. The data used in this research is secondary data in the form of a time series starting from 2019 to 2023 (per month). The research method used is the VECM method and Granger causality. The research results are Based on the research results, the variables that have a long-term relationship are the price of soybeans (X2) and the price of purebred chickens (X3) as evidenced by the T-statistic value > from the t-table. In the short term, several variables, namely the price of corn (X1-1) at lag 1, the price of soybeans (X2-2) at lag 2, the price of chicken (X3-1) and general inflation (Y-2) at lag 2 have an effect on general inflation. (Y). This is because each variable has a t-statistic value > t-table. Based on the results of the Granger causality test, there is a one-way causality relationship between the variables corn price (X1) and soybean price (X2). one-way causality between the variable corn price (X1) and general inflation (Y), one-way relationship between the variable broiler chicken (X3) and the price of soybeans (X2), one-way relationship between the variable price of garlic (X4) and the price of soybeans (X2 ), a one-way relationship between the soybean price variable (X2) and the inflation variable (Y), a one-way relationship between the price variable for purebred chickens (X3) and general inflation (Y).